Can we avoid casting for suspected scaphoid fractures? A multicenter randomized controlled trial - Abigael Cohen; Max Reijman; Gerald A. Kraan; Sara J. Baart; Jan A. N. Verhaar; Joost W. Colaris; the SUSPECT study group (Journal of Orthopaedics and Traumatology)
Abstract Background In suspected scaphoid fractures with normal initial radiographs, the usual care is casting, but only 10% of patients have scaphoid fractures. To reduce overtreatment, we evaluated whether bandaging, instead of casting, resulted in noninferior functional outcomes. Patients and methods We included adults with suspected scaphoid fractures and normal initial radiographs at the emergency department in our multicenter randomized controlled trial. Patients were randomized to 3-day bandaging or 2-week casting. Questionnaires, physical examination, and radiographs were performed at 2 weeks and 1 year. Additional questionnaires were sent after inclusion, 6 weeks, and 3 months. Our primary outcome was the adjusted estimated difference between groups of the Quick Disabilities of the Arm, Shoulder, and Hand (QDASH) score at 3 months (natural logarithm of the margin of noninferiority = 2.0). Secondary outcomes included the QDASH score, Patient-Rated Hand/Wrist Evaluation Score, visual analog scale pain, wrist range of motion, patient satisfaction, and complications during follow-up. Results Of the 180 patients (91 bandaging and 89 casting), 16 had scaphoid fractures and there were no scaphoid nonunions. Functional outcome in the bandaging group was noninferior at 3 months compared with the casting group [adjusted estimated difference QDASH score 0.30 (95% CI 0.02–0.62)]. All other patient-reported function and pain scores were not significantly different between groups. Range of motion at 2 weeks was better in the bandaging group, and they were more satisfied with the treatment than the casting group. Conclusions Casting for suspected scaphoid fractures but normal initial radiographs can be avoided because bandaging seems to be an alternative treatment option when patients are reevaluated after 2 weeks. Level of evidence Level II. Trial registration Trial registered at the Trialregister on 2018-02-28 on www.trialregister.nl , NTR7164